The role of worst pattern of invasion in the prognosis of oral cavity malignancies - Campbell, Brett; Gundale, Abhijit; Cap, Maximiliano Ramia de; Kaul, Sumedh; Gomez, Ernest; Nishino, Michiya; Jalisi, Scharukh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Our study aimed to assess the significance of worst pattern of invasion (WPOI) and its effect on survival in oral cavity squamous cell carcinoma (OCSCC). Methods: This is a retrospective study of patients with OCSCC who underwent surgery. Univariate and bivariate analysis were used to analyze the association between WPOI and demographics, tumor characteristics and treatment. The association of WPOI with overall survival was evaluated. Results: The 3-year OS was 77% for WPOI ≤4 and 70% for WPOI 5 (p=0.5). In the tongue subsite, the 3-year OS was 81% for WPOI ≤4 and 57% for WPOI 5 (p=0.08). WPOI-5 showed significant association with perineural invasion (p<0.01), lymphovascular invasion (p<0.01), lymph node involvement (p<0.03), and higher depth of invasion (p<0.01). Conclusion: WPOI-5 may be considered a prognostic factor in deciding treatment in the post-surgical setting, and my become a mandatory parameter in pathology synoptic reports in the future.